Demulsification Of Emulsion Effluent Using Modified Palm Oil Fuel Ash (Pofa) - Manogaran, Sathis Kumar (Universiti Sains Malaysia, 2022)
Oil and Grease is a common issue arising in the food industry wastewater treatment plant. The complications from it can be greatly reduced by separating the oil in water emulsion into two distinct phases. Thus, in order to fulfill the purpose, an effective and cheap demulsifier is required and Palm oil fuel ash (POFA) which is a prominent palm oil industrial byproduct in nations such as Indonesia and Malaysia considered propitious. It exhibits significant potential to be employed as a demulsifier owing to its outstanding structure , availability, and cost-effective properties. This study investigates the optimum modification to be done on POFA as a demulsifier including thermal and chemical treatment to result in an outstanding performance during the demulsification process of oil in water emulsion. To analyze the properties such as morphology and porosity of the pristine POFA and modified POFA before and after demulsification, characterization studies were carried out via Fourier transformed infrared (FTIR) spectroscopy and BET surface area analysis. Modification via chemical treatment demonstrated better demulsification efficiency compared to thermal treatment due to the more porous structure and increased surface area of POFA. The effects of different process parameters including demulsifier dosage and contact time were analyzed via batch demulsification study at fixed temperature of 30 °C and emulsion concentration of 5000 ppm. An optimum demulsification efficiency was obtained using 1.5g of POFA for 120 minutes. An outstanding separation efficiency by modified POFA was observed on emulsion stabilized by sorbitan tristearate (STS) emulsifier compared to polyglycerol esters (PGE) emulsifier. It is certainly proved that POFA will be a promising and economically feasible demulsifying agent to be utilized in treating oil in water emulsion from food industries.